Liprin-α4 is a new hypoxia-inducible target gene required for maintenance of cell-cell contacts - Mattauch, Sandra; Sachs, Martin; Behrens, Jürgen (Experimental Cell Research, 2010)
Liprin-α1 to liprin-α4 constitute a family of cytoplasmic proteins, which have been found in various multiprotein complexes. For liprin-α1 roles in synapse formation and cell spreading were described but other liprin family members are not well characterized. We show here that liprin-α4 is upregulated in human clear cell renal cell carcinomas (RCC) as compared to normal kidney tissue. Liprin-α4 expression is downregulated by the von Hippel-Lindau tumor suppressor (VHL) and upregulated by hypoxia in RCC cell lines. The liprin-α4 gene promoter is directly activated by binding of the hypoxia-inducible factor 1α (HIF-1α) to HRE consensus binding sites as shown by reporter assays and chromatin immunoprecipitations. RNAi mediated knockdown of liprin-α4 leads to reduced E-cadherin and Β-catenin levels at cell junctions and to dissociation of epithelial cell contacts. Our data describe for the first time liprin-α4 as a hypoxia-induced gene potentially involved in cell-cell adhesion. © 2010 Elsevier Inc.
Created from Fastlane, Scopus look-up
Keywords: Cell-cell contacts; E-cadherin; HIF; Liprin; RCC; VHL

Molecular signature for lymphatic metastasis in colorectal carcinomas. - Croner, Roland S.; Förtsch, Thomas; Brueckl, Wolfgang M.; Roedel, Franz; Roedel, Claus; Papadopoulos, Thomas; Brabletz, Thomas; Kirchner, Thomas; Sachs, Martin; Behrens, Jürgen; Klein-Hitpass, Ludger; Stürzl, Michael; et al. (Annals of Surgery, 2008)
Fifty differently expressed genes between stage UICC I, II versus III CRC were identified respecting the selection criteria by allowing for multiple testing. The data validation by the independent clinical study confirmed our results. In comparison to MC, the genes were over- or underexpressed. They belong to various functional groups such as cellular adhesion, transporters, signaling, metabolism, protein synthesis, gene control, and immune system. Forty tumor samples of stage UICC I, II CRC, 40 samples of stage III CRC, and 25 biopsies of healthy mucosa (MC) were shock frozen in liquid nitrogen and underwent cryotomy after manual dissection for tumor tissue or MC enrichment. Isolated RNA was hybridized to GeneChips (HG-U133A, Affymetrix). Preprocessing of the microarray results was done by the robust multichip average method, and differentially expressed genes were selected by the maximum Wilcoxon statistic over 22,215 probe sets. The results were validated at an independent clinical study. Our large patient cohort and the data validation on an independent study identified 50 differentially expressed genes between CRC of different histopathologic stages. These findings indicate that molecular staging of CRC may be possible, which could help to guide individual CRC treatment before surgery. TNM-staging of colorectal carcinomas (CRC) relies on the histopathologic workup of the surgically removed specimen. If valid preoperative staging methods existed, patients could be selected for adequate individual therapy before surgery. Microarray techniques provide a promising tool to identify stage-specific molecular signatures on primary tumor biopsies. RESULTS MATERIAL AND METHODS CONCLUSION PURPOSE